GISP2 (D Core) Methane Concentration Data - Brook, Edward J (IEDA: US Antarctic Program Data Center, 2008)
Abstract: This ice core data is archived at the World Data Center for Paleoclimatology and is available through the Ice Core Data Gateway. The data includes methane data from the Greenland Ice Sheet Project 2 (GISP2). GISP2 is an ice core project that drilled through the Greenland ice sheet and 1.55 meters into bedrock. The ice core is 3053.44 meters in depth, the deepest ice core recovered in the world at the time. The ice core was completed in 1993 after five years of drilling. Methane concentrations were determined by GC-FID using standards calibrated by NOAA CMDL. The gas age time scales and analytical techniques are described in further detail in the publication.